2009
DOI: 10.4067/s0716-078x2009000100011
|View full text |Cite
|
Sign up to set email alerts
|

Hongos ectomicorrícicos y la tolerancia a la salinidad en plantas

Abstract: RESUMENEl proceso de salinización de los suelos constituye un problema generalizado a nivel global. En este sentido, los hongos ectomicorrícicos tienen una importante participación en la recuperación de suelos forestales ya que involucran una serie de mecanismos celulares que pueden contribuir a la tolerancia a la salinidad en plantas que habitan los bosques templados o boreales. La participación de los hongos ectomicorrícicos en la tolerancia a la salinidad involucra la regulación homeostática de los iones, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The interactions between soil, plant roots, and different soil microbes play important roles in regulating metal movement from soil to edible parts of crops and may represent this way an important tool to increase the uptake of required essential elements and/or to decrease the uptake of toxic metals by the plants in soils with unbalanced metal concentrations (e.g., Islam et al 2007;Ma et al 2009; reviewed by Burleigh and Bechmann 2002;Hall 2002;Aguilar-Aguilar et al 2009;Lemanceau et al 2009;Wenzel 2009). Similarly, the way of irrigation and of course fertilization may also influence metal uptake by plants and their distribution between shoots and roots (Singh and Sinha 2005;Gupta and Sinha 2006;Nair et al 2008); therefore, it should be considered in sustainable agricultural practice.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between soil, plant roots, and different soil microbes play important roles in regulating metal movement from soil to edible parts of crops and may represent this way an important tool to increase the uptake of required essential elements and/or to decrease the uptake of toxic metals by the plants in soils with unbalanced metal concentrations (e.g., Islam et al 2007;Ma et al 2009; reviewed by Burleigh and Bechmann 2002;Hall 2002;Aguilar-Aguilar et al 2009;Lemanceau et al 2009;Wenzel 2009). Similarly, the way of irrigation and of course fertilization may also influence metal uptake by plants and their distribution between shoots and roots (Singh and Sinha 2005;Gupta and Sinha 2006;Nair et al 2008); therefore, it should be considered in sustainable agricultural practice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, similar findings were mentioned by Bano and Fatima (2009) on Zea Maize, Karlidag et al (2013) on strawberry and Ullah et al (2016) on tomato, who observed that PGPR decreased EL in cells of plants suffer from salinity stress. Among the roles of biofertilizers (particularly AM) as salinity alleviation treatment used in this study is to enhance the synthesis of antioxidant enzymes (Aguilar-Aguilar et al, 2009) and also increase their activity (Heikham et al, 2009) for scavenging of ROS. Also, Rady et al (2016) found that application of organo-mineral fertilizer compost significantly reduced EL in bean plants which grown in saline soil.…”
Section: -Electrolyte Leakage (El)mentioning
confidence: 99%
“…6 "Los hongos ectomicorrícicos son organismos que proporcionan amplios beneficios a la planta, debido a una compleja red de mecanismos que le confieren la capacidad de suministrar nutrientes y crecer en ambientes salinos, en plantas que habitan los bosques templados o boreales" (Aguilar et al 2009:1) 7 "El cepario de INECOL fue fundado en 1982 y está registrado en el World Data Centre for Microorganisms con el número 782 y las siglas IE". (Mata et al, 2016: 697).…”
Section: Investigación Fúngica En Méxicounclassified